2022
DOI: 10.37871/jbres1400
|View full text |Cite
|
Sign up to set email alerts
|

Current Knowledge and Awareness of Dengue Fever among Students of Government College University Faisalabad

Abstract: Background: Dengue fever is a vector-borne infectious tropical disease caused by the dengue virus, the most common arthropod-borne infection in humans. According to WHO, the best strategy to avoid dengue endemic is to educate people about the disease and preventative measures? Despite the efforts to avoid the dengue virus, the newest national survey statistics show that dengue fever is still on the increase among the population. The major goal of this study was to examine university students' knowledge of deng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 19 publications
(18 reference statements)
3
7
0
Order By: Relevance
“…Only 35.5% of the students knew about the biting time of Dengue mosquito. Mixed responses on this have been recorded in other studies; studies (6,15) reported higher percentages, studies (14,16,18,20) reported medium percentages and studies (11,12,21) reported low percentages. Students in our study had good knowledge (95.1%) about the breeding sites.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Only 35.5% of the students knew about the biting time of Dengue mosquito. Mixed responses on this have been recorded in other studies; studies (6,15) reported higher percentages, studies (14,16,18,20) reported medium percentages and studies (11,12,21) reported low percentages. Students in our study had good knowledge (95.1%) about the breeding sites.…”
Section: Discussionmentioning
confidence: 49%
“…The research will serve as a tool to generate new strategies within the community and among the students and will also facilitate in formulation of pragmatic recommendations that can impart awareness about the severity and prevention of the disease. Keeping in view previously conducted similar awareness studies (6,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), an online close-ended structured questionnaire was formulated and shared among the students using nonprobability convenience method. The questions were based on "correct", "incorrect" and "unaware" responses ("unaware " option was counted as an incorrect response).…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy in results can be explained based on the research conducted on the students of Government College University Faisalabad regarding level of awareness. The results of that study showed a poor level of awareness among the students of Government College University Faisalabad and thus it was concluded that the level of awareness regarding dengue is poor in southern Punjab 12 which explains the moderate level of dengue awareness instead of a high level of dengue awareness among the faculty members of Government College University Faisalabad.…”
Section: -35 Good 30%mentioning
confidence: 86%
“…These factors create ideal conditions for DVI transmission in the country [ 4 6 ]. Pakistan has reported more severe dengue cases due to condensation in inter-epidemic periods [ 3 , 5 7 ]. According to the National Institute of Health (NIH) Islamabad, the number of cases reported in Pakistan in 2017, 2018, 2019, and 2020 were 22,938, more than 3,200, 24,547, and 3,442, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are dearth of investigations evaluating risk factors of DHF in Pakistan. Other studies conducted in Pakistan focus on the clinical profile of the dengue infection [ 9 ], have small sample size [ 5 , 10 ], clinical and laboratory features of the disease [ 7 ], association of DVI with thrombocytopenia and leucopenia [ 8 ], dengue serotypes [ 11 ], and detection of DVI using immunoglobulins and nonstructural protein 1 (NS-1) antigens [ 12 ].…”
Section: Introductionmentioning
confidence: 99%